Prevalence of Latent Tuberculosis Infection in the Middle East and North Africa: A Systematic Review - Barry, Mazin (Pulmonary Medicine, 2021)
Objective. Data on the prevalence of latent tuberculosis infection (LTBI) in Middle Eastern and North African countries are scarce. We aimed to review all relevant published data in countries belonging to this region to determine the overall prevalence of LTBI in the Middle East and North Africa (MENA) region. Methods. In this systematic review PubMed and Google Scholar databases were searched for observational, prospective, retrospective, cross-sectional, and cohort studies providing prevalence data of LTBI in any MENA country. Studies fulfilling the search criteria were incorporated in the review. Overall prevalence of LTBI with 95% confidence intervals (CI) was calculated using the random-effects model; heterogeneity was assessed using I2 statistics. Gender and age group-based subgroup analyses were performed to evaluate the basis of heterogeneity. Results. The total number of overall LTBI studies identified was 956, of which 31 studies from ten countries within the MENA region were included that represented 12,439 subjects. The overall prevalence was 41.78% (95% CI 31.18% to 52.78%, I2=99.31%). By gender-based subgroup analysis, the prevalence of LTBI was 33.12% (95% CI 18.97% to 49.04%, I2=99.25%) and 32.65% (95% CI 19.79% to 47%, I2=98.89%) in males and females, respectively, while in the age-based subgroup analysis, the prevalence of LTBI was 0.44% (95% CI -0.05% to 0.9%), 3.37% (95% CI 2.23% to 4.74%, I2=0%), and 43.81% (95% CI 33.09% to 54.82%, I2=99.18%) for children, adolescents, and adults, respectively. Conclusion. This systematic review reveals a high prevalence of LTBI in the MENA region; enhanced LTBI surveillance and prompt infection prevention steps are urgently needed to prevent active tuberculosis, this would help achieve the World Health Organization End TB Strategy 2035, and the United Nations Sustainable Development Goals 2030 target in the MENA region.